Phonological Processes of Hindi Loanwords in Indonesian: A Comparative Study with Indian Languages - Pauzan Pauzan; Muhamad Zulpiani Hamdi (ITScience (Information Technology and Science), 2026)
The primary objective of this study was to examine the phonological processes involved in the adaptation of Hindi loanwords into Indonesian. To achieve this goal, the researcher employed a qualitative descriptive approach, relying on documented data of Hindi loanwords as used in Indonesian. The data set consisted of lexical items presented in phonetic transcription, which facilitated systematic phonological analysis. The study's findings revealed two central aspects of the adaptation process. The first aspect concerns vowels, where three main phonological processes were identified: lowering, weakening, and shortening. Lowering, often referred to as vowel drop, involves the modification of vowel height within the vowel space. In contrast, weakening refers to the reduction in the strength or prominence of a vowel sound. Shortening further indicates the reduction of vowel duration in specific contexts. The second aspect pertains to consonantal processes, which include several modifications such as epenthesis, de-affrication, de-aspiration, consonant deletion, alveolarization, and the velarization of nasal sounds. These processes demonstrate the structural adjustments required to integrate Hindi phonological forms into the phonetic system of Indonesian. In summary, the study concludes that phonological adaptation in Hindi loanwords encompasses two major domains: vowel processes and consonant processes, each contributing to the naturalization of borrowed lexical items.